Increasing Chitinase Activity of Serratia marcescens PT-6 through Optimization of Medium Composition - Akhmad Awaludin Agustiar; Imas Faturrohmah; Bekti Wulan Sari; Nurul Binti Isnaini; Indun Dewi Puspita; Triyanto Triyanto; Amir Husni; Ustadi Ustadi (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2019)
Chitin hydrolysate is one of the value added product derived from shrimp shell waste. Production of chitin hydrolysate using biological process offers an environmental friendly method compared to chemical process. Serratia marcescens PT-6, a gram negative chitinolytic bacterium isolated from shrimp pond sediment, shows good activity in hydrolyzing chitin. This study aimed to improve the chitinase activity of S. marcescens PT-6 culture by optimizing the component of chitin-containing medium (additional nitrogen source, additional carbon source, and colloidal chitin). The optimization of chitinase by S. marcescens PT-6 culture was done using one variable at a time method. The sequence of the research were to optimize 1) the type of additional carbon source (glucose, lactose, sucrose, and starch), 2) the type of additional nitrogen source (yeast extract, peptone, ammonium sulphate, and ammonium chloride), 3) the concentration of colloidal chitin (0.5; 1; 1.5; 2; and 2.5%), and 4) the concentration of the additional carbon and nitrogen source. The culture of S. marcescens PT-6 was incubated in colloidal chitin medium at 30 oC and chitinase activity from culture supernatant was analyzed. The results showed that starch gave the highest chitinase activity compare to other carbon source, meanwhile yeast extract was chosen as the best nitrogen source among others. The combination of 1.5% colloidal chitin with 0.5% starch and 0.1% yeast extract in medium increased the chitinase activity of S. marcescens PT-6 to 0.021 U/ml. These results indicated that an appropriate medium composition could increase the chitinase activity produced by S. marcescens PT-6 culture.